Portable Network Aquisition System using Single Board Computer & GNU/Linux - Md. Mostafijur, Rahman; R. Badlishah, Ahmad, Dr.; Salina, Mohd Asi; Zahereel Ishwar, Abdul Khalib; W.M.A. Mamat; Ahmed Nasir, Che Rosli (Universiti Malaysia Perlis (UniMAP), 2008)
Organized by Universiti Malaysia Perlis (UniMAP), 15th - 16th March 2008 at Putra Brasmana Hotel, Perlis.